Comparison of structure and turbulent mixing between lateral and leading-edge river plume fronts: Microstructure observations from a T-REMUS AUV. (5th April 2023) - Delatolas, Nikiforos; MacDonald, Daniel G.; Goodman, Louis; Whitney, Michael; Huguenard, Kimberly; Cole, Kelly
Abstract: The energetic frontal region of the tidally pulsed Connecticut River plume was sampled with the T-REMUS Autonomous Underwater Vehicle (AUV) which navigated ten cross-front transects at various depths. Synchronous and high resolution hydrographic, microstructure, velocity and backscatter observations allowed the creation of detailed views of frontal structure and turbulent mixing in the reference frame of the propagating front. The front was defined by a sharp horizontal density gradient of ∼18.5 kg m −4 across only 0.7 m in the horizontal, and strong downwelling velocities of 0.17 m/s. Three successive zones were consistently identified. The first O (10 m) wide downwelling zone in which buoyant plume water was forced downward, thereby forming a highly energetic frontal head that extended down to 6 m depth and had TKE dissipation rates (ε) of order 10 −3 m 2 /s 3 . Beyond the downwelling zone to O (100 m), a transition zone was observed, characterized by substantial entrainment of ambient water. This zone had high amplitude and high frequency density anomaly (σθ ) variability consistent with elevated but decreasing turbulent kinetic energy dissipation rates (ε) which ranged between 10 −4 and 10 −5 m 2 /s 3 . Beyond O (100 m) from the front, stable stratification, high Ri values, and low Reb values, suppressed the growth of instabilities and diminished turbulent mixing. In this stable interior region the plume base shoaled to 2 m depth and ε decreased further, from 10 −5 to 10 −7 m 2 /s 3 . In ambient Long Island Sound waters, ε ranged between 10 −6 and 10 −7 m 2 /s 3 . The cross-front distributions of σθ and ε did not change substantially as the front transformed from a lateral boundary, where plume flow was primarily in the along-front direction, to one that was at the leading edge of the plume, where plume flow was mostly in the cross-front direction. In both cases, a significant convergence was present at the front due to strong ambient tidal velocities. The observed ε values and those from four previous studies of large and mid-sized plumes were nondimensionalized using the velocity and length scales associated with the downwelling region at the front. The effective normalization suggests that local dynamics primarily control ε in the near-frontal region. Highlights: Frontal structure consists of a downwelling zone followed by a trailing frontal zone. Frontal structure is similar between lateral and leading edge fronts. Turbulence peaks in the downwelling zone and diminishes in the trailing frontal zone. Frontal turbulence from various systems collapses using a frontal feature scaling.